First Lumbar Treatment of Chronic Mixed Low Back Pain with High Dose Capsaicin 8% Patch - Julian, Prosenz; Stefan, Neuwersch; Herwig, Kloimstein; Rudolf, Likar; B., Gustorff (International Journal of Pain Management, 2017)
Background Capsaicin 8% patch reduces peripheral neuropathic pain. Based on the concept of neuropathic pain (NeP) in mixed low back pain (LBP) it is hypothesized, that an exclusively lumbar capsaicin 8% patch is an effective treatment of mixed LBP. The aim is a proof of this concept and to identify predictors of responsiveness. Methods This prospective stratified study included 54 chronic, mixed, LBP patients with spontaneous pain >3/10 on the NRS (0-10) and a painDETECT Questionnaire (PDQ) score >12 meaning possible or likely (>18) NeP. Pain intensity, PDQ, and quantitative sensory testing (QST) were assessed at baseline. After a one-hour capsaicin 8% treatment on the low back, follow-up was carried out regularly over three months. Response was determined at one month (≥30% pain reduction) and predictors were compared accordingly. Results The average change in pain intensity at week four was -1.1 (-0.50;-1.71, 95%CI, p < 0.001). Twenty-one (39%) patients responded at one month with a mean pain reduction of -3.1 (-4.0;-2.3, 95%CI) and even 10 of the 21 responders showed a ≥ 50% pain reduction. No pain reduction was seen in 33 (61%) patients (p = 0.42). Responders and non-responders did not differ at any baseline parameter: NRS (p = 0.85), PDQ score (p = 0.47), duration of pain (median of 48 and 36 months) nor QST profiles. Conclusions Lumbar capsaicin 8% patch is an effective treatment in about 40% of chronic patients with mixed neuropathic LBP. However, predictors for response could not be identified.
Keywords: Chronic pain; mixed low back pain; capsaicin patch; neuropathic pain; treatment